Genealogie in der Moderne Akteure - Praktiken - Perspektiven - Timm, Elisabeth; Hecht, Michael (Cultures and Practices of Knowledge in History, 2022)
What was the significance of searching for and finding "family" and kinship through the ages? Which methods and strategies did actors use to produce relational connections, and into what structures and discourses can these practices be categorized? This volume takes up new insights from research into premodernity based on the history of knowledge and praxeology.